1968
DOI: 10.1002/1097-0142(196805)21:5<945::aid-cncr2820210519>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy in cancer of the lung

Abstract: Microscopic studies of two cases of keratinized squamous cell carcinoma, several cases of small cell carcinoma and one of adenocarcinoma of the lung are described and illustrated. The authors suggest that pulmonary tumors which are not readily classified by light microscopy might be classified by electron microscopic examination under one of the main groups of bronchogenic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Although neoplastic squamous cells showed non‐keratinization histologically, the electron microscopic demonstration of tonofilaments and desmosomes suggested that the tumour was a moderately differentiated squamous cell carcinoma. These findings were similar to those reported in humans (Obiditsch‐Mayer and Breitfellner, 1968; Kimula, 1978).…”
Section: Discussionsupporting
confidence: 92%
“…Although neoplastic squamous cells showed non‐keratinization histologically, the electron microscopic demonstration of tonofilaments and desmosomes suggested that the tumour was a moderately differentiated squamous cell carcinoma. These findings were similar to those reported in humans (Obiditsch‐Mayer and Breitfellner, 1968; Kimula, 1978).…”
Section: Discussionsupporting
confidence: 92%
“…Secretion granules were not present and cytoplasmic organelles, other than mitochondria and free ribosomes, were poorly developed. These anaplastic tumor cells shared many ultrastructural characteristics with the small ("oat") cell type of bronchogenic carcinoma that has been reported previously (27)(28)(29). They could be readily differentiated from squamous cell carcinomas of the lung by the lack of tonofilaments and keratohyaline glanules, and from pulmonary adenocarcinomas by the absence of acinar formation with microvilli and large secretory vacuoles (28).…”
mentioning
confidence: 57%
“…G. L. WHITELAW Fronm the Department of Pathology, University of Cambridge, Cambridge * Received for publication October 10, 1968 ELECTRON microscope studies of oat cell carcinoma of the bronchus have been carried out by several groups of workers (Laval, 1966;Nagaishi et al, 1965;Obiditsch-Mayer and Breitfellner, 1968; Pariente, Even and Brouet, 1966;Stoebner et al, 1967). No electron microscope paper has yet been published on a bronchial carcinoma known to be secreting antidiuretic hormone.…”
Section: Ultrastructure Of An Oat Cell Carcinoma Of the Bronchus Prodmentioning
confidence: 99%